2021
DOI: 10.1051/e3sconf/202125409007
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrat-fat metabolism disorder in cows and calves

Abstract: Inconsistencies in feeding level of dairy cattle to their feed needs leads to various metabolic diseases, including ketosis. The purpose of our work is to study changes in the metabolism of both sexually mature representatives of dairy cattle and young animals obtained from them. The article states the following causal factors of ketosis occurrence in cows: excessive amount of fat substances, imbalance of various chemical elements in feeding diet. The pathology of carbohydrate-fat metabolism during ketosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In the authors' opinion, this circumstance is explained by the improvement and increase of metabolic processes in lactating cows by providing their body with a sufficient amount of plastic material for the synthesis of high-quality milk. This research is confirmed by the results of other authors who noted improvements in cattle productivity with the introduction of biologically active additives [12][13][14].…”
Section: Research Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the authors' opinion, this circumstance is explained by the improvement and increase of metabolic processes in lactating cows by providing their body with a sufficient amount of plastic material for the synthesis of high-quality milk. This research is confirmed by the results of other authors who noted improvements in cattle productivity with the introduction of biologically active additives [12][13][14].…”
Section: Research Resultssupporting
confidence: 88%
“…The research results of many scientists in the field of animal husbandry indicate a direct dependence of the level of cows' dairy productivity on their bodies' provision degree with energy, protein, easily digestible carbohydrates, vitamins, macro-and microelements and the development of pathologies with their imbalance in the diet [9].…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, its environment, the ratio of volatile fatty acids and the activity of microorganisms play an important role in the normal course of digestion of nutrients in the large intestine. When cattle are fed a balanced diet, the ratio of volatile fatty acids in the large intestine is as follows: acetic acid 65%, propionic acid 20%, fatty acid 15% [7,9].…”
Section: Main Partmentioning
confidence: 99%
“…Timely implementation of therapeutic and preventive measures allows to ensure the receipt of healthy livestock and, as a result, high-quality livestock and poultry products, regardless of the forms of ownership of enterprises [4,5,6]. The processes of changing the ecology of pathogens and diseases, the emergence of new infectious diseases require today a more thorough scientific analysis and generalization, the early development of prevention and control measures.…”
Section: Introductionmentioning
confidence: 99%